Economic and Financial Analysis of Cofiring the Coal Fired Steam Power Plant Capacity 660 MW with Biomass - Widya Faisal Wahyudi; Iwa Garniwa M.K. (Andalas Journal of Electrical and Electronic Engineering Technology, 2021)
Research on Cofiring of the Existing Coal Fired Power Plant with biomass in the form of sawdust with a mixture percentage of 5% was carried out with the main objective of pursuing the acceleration of the renewable energy mix target of 23% (Green Booster) by 2025, with minimal CAPEX costs if compared to building new hydro or solar PV plants. At the initial stage of the activity, testing and analysis of the effect of cofiring will be carried out on several main parameters of the Existing PLTU's performance, as well as its reliability. In addition, it is also at the same time to get an overview and evaluate if the cofiring plan will be implemented through technical operational evaluations, the cost of production from the aspect of fuel costs (component C) and exhaust emissions to the environment. From the results of monitoring the operating load at around 635 MW (gross) using 5% cofiring, it can be seen that critical points such as main steam temperature, main steam pressure, gas economizer outlet temperature, mill outlet temperature do not show a significant increase, meaning they are still within the operating limits, reasonable and safe. From the calculation of the cost of fuel, the coal price is IDR 594 per kg, and sawdust price of IDR 472 per kg (on site) using the SFC difference of 0.0077 kg/kwh, and the CF assumption of 80%, then with an average annual electricity production of 4,415,040,000 kwh/year, fuel savings of around IDR 35.32 billion per year will be obtained. Exhaust gas emissions to the environment for SO2 and NOx still meet the environmental quality standard requirements according to the Minister of Environment and Forestry Regulation No.15 of 2019.